Pengaruh Teori Fraud Pentagon Terhadap Terjadinya Fraudulent Financial Reporting dengan F-Score - Eneng Naelul Yulia Ningsih; Ahmad Syarief (Indonesian Accounting Literacy Journal, 2021)
This study aims to examine the effect of risk factors for fraud in the theory of fraud pentagon using the F-Score Model. The independent variables used are financial stability (A), ineffective monitoring (B), auditor switch (C), change of directors (D), and frequent number of CEO's picture (E) with the dependent variable being fraudulent financial reporting (Y). . This study uses quantitative methods from secondary data, namely the company's annual report. The sample in this study were 23 state-owned companies listed on the Indonesia Stock Exchange in 2015-2019 which were selected using the purposive sampling method. The analysis used is Panel Data Regression with the E-Views 11 program and the help of SPSS 25. The results show that A, B, C, D, and E have a simultaneous effect on Y. But partially, variables A, C, E have an effect on significant to Y. While B, D have no effect on Y.